THE OPPORTUNITY OF USING CLOUD-BASED COMPUTING IN NUMERICAL SIMULATIONS ON STRUCTURAL ANALYSIS - CASE STUDY - VLAD ANDREI CIUBOTARIU; COSMIN GRIGORAS; CRINA MARIA RADU; CATALIN NICOLAE TAMPU; VALENTIN ZICHIL (Journal of Engineering Studies and Research)
To make the most accurate behavioral assessments of mechanical parts, engineers rely heavily on numerous software solutions. These software solutions are able to solve more or less complex problems with a fairly high degree of accuracy and similarity to physical experiments. The common feature of these software solutions is that they need generous resources from the computer on which they are installed. Can't it be done differently? One possible answer may be the use of cloud-based solutions. The main purpose of this paper is to make a comparison and find the limitations of such a solution relative to the established ones in the field of finite element analysis. Therefore, this paper is a case study in which an industrial component – beam bracket – is subjected to a structural analysis on three different software solutions. The reference systems are: ANSYS, a solution dedicated to finite element analysis and SolidWorks Simulation, a solution often used in industry for the assessment of mechanical structures. The cloud-based solution is SimScale, a software product based on open-source codes: Code_Aster and CalculiX.